2007
DOI: 10.1111/j.1600-0404.2007.00882.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma levels of cytokines after seizures in localization-related epilepsy

Abstract: These results show that only single seizures cause activation of cytokine cascade and associated inflammatory signals. In the case of recurrent seizures, these signals may result in structural changes in the nervous tissue, which are generally associated with drug refractory epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
85
5
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(98 citation statements)
references
References 12 publications
4
85
5
4
Order By: Relevance
“…This study shows the importance of epilepsy type in determining the chronic overproduction of IL-6 in refractory epilepsy, whereas our previous studies have demonstrated the acute activation of the cytokine network following seizures [8,9,20,21]. All patients with increased levels of IL-6 had TLE, which is known to be the most common epilepsy type refractory to drugs.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…This study shows the importance of epilepsy type in determining the chronic overproduction of IL-6 in refractory epilepsy, whereas our previous studies have demonstrated the acute activation of the cytokine network following seizures [8,9,20,21]. All patients with increased levels of IL-6 had TLE, which is known to be the most common epilepsy type refractory to drugs.…”
Section: Discussioncontrasting
confidence: 66%
“…However, the significance of clinical characteristics of epilepsy has not been well established in patients with possible immunological alterations. In our previous studies, titres of IL-6 measured at the beginning of video-EEG recordings before documented seizures and those measured between documented seizures during the recording have tended to be higher in patients with chronic epilepsy compared with healthy controls [20,21]. We have previously demonstrated an immediate effect of seizures on concentrations of IL-6 and to a lesser extent IL-1RA; the duration of this effect was less than 24 h. In this study, we aimed to assess long-term effects of seizure frequency on prevalence of IL-6 and IL-1RA.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, if VNS only inhibits cytokine expression in the immediate postictal phase, this effect would not be detected using the present study design. Although it is technically challenging, future studies should compare cytokine levels immediately before and after a seizure [35,36]. …”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have revealed that the levels of cytokines IL-6, IL-1 ␤ and IL-1ra are increased in serum or plasma after seizures [11][12][13][14] . In cerebrospinal fluid (CSF), only increased levels of IL-6 were evident after single tonic-clonic seizure, whereas IL-1 ␤ and IL-1ra levels remained unchanged [2,11] .…”
Section: Introductionmentioning
confidence: 99%